Estudo sobre a distribuição da malária no Pará e sua correlação com fatores ambientais e socioeconômicos - FERNANDES, Willian Ricardo da Silva (Universidade Federal do Pará, 2013)
The malaria is a parasitic disease caused by Protozoa of genus Plasmodium that completes its complex cycle of development alternating between human hosts and mosquitoes of the genus Anopheles. In the world-wide context, it constitutes a serious problem of public health that mainly affects the developing countries of tropical and subtropical climate. In Brazil, one gives credit that 99.5% of the registered cases of malaria meet in the Legal Amazonian. Much of the success of this complaint in this region must it biological and environmental factors that favor levels high of vectors, beyond social factors that compromise the efforts to control the disease. Thus, the objective of this work was to study the profile epidemiologist of the malaria in Pará, during a historical series (1999 - 2003), analyzing the influence of environmental and socioeconomic variable on the prevalence of the cases. For such the annual parasitic indices (IPA) of each city had been calculated and, through a SIG, these data they had been georreferencied and studied of temporal and spatial form. Data on the deforestation in the State had been analyzed, through a regression for permutation, to try to explain the temporal variation of the malaria. For the spatial study (multiple regression) the influence of the variable: temperature, rainfall, altitude, education, longevity and income; was tested on the prevalence of the malaria. In the secular study the malaria presented a decreasing trend in the State, however, only 31 cities had presented the same trend, did not have increasing trend, the 112 remaining cities had presented steady trend. Moreover, many cities had alternated increase and reduction of the cases throughout the series, having indicated a good action of control, but a weak performance of the monitoring. In this context the deforestation seems to influence the secular series of the malaria, was gotten resulted significant in two (2001 and 2002) of the three studied years. In the space study the adopted final model, although a low clarifying power (R²=0.31), presented three significant variable: number of dry months, income and education. However, the result of the two first ones is not presented of a direct form, being reflected of other activities. Although the scale adopted and of problems in the aggregation of the data (they are only available for city), this work presents resulted excellent that can assist the managers of the health (or endemic diseases) to direct action of control for the pointed areas as critical, acting in the factors of bigger significance, thus getting better exploitation of available the human resources and material.